THE EXISTENCE OF GROUPS OF METEORITE-PRODUCING FIRE-BALLS AND METEORITES IN COMET-LIKE ORBITS - Konovalova, N. A.; Gorbanev, Yu. M.; Davruqov, N. H. (Одеські астрономічні публікації, 2018)
This paper discusses the existence of groups of meteorite-producing fireballs and ordinary chondrites in the Earth-crossing Jupiter-family comet-like (JFC) orbits. The similarity of the orbits of meteorite-producing fireballs and those of meteorites in the groups was established by applying three criteria of orbital similarity – namely, the DSH criterion introduced by Southworth and Hawkins, the DDR criterion suggested by Drummond, and DN criterion reported by Jopek. We have detected six groups of meteorite-producing meteoroids and ordinary chondrites of L3.5-H5 types observed over the determined periods of increased fireball activity. Carrying out systematic and well-targeted observations, especially during the determined periods of increased fireball activity, enables to obtain reliable statistics from the collected observational data on the meteorite-producing meteoroids in order to determine their orbits, as well as their physical characteristics. The six target groups in this study, which contain 89 meteorite-producing meteoroids and six ordinary chondrites, may be groups of dynamically connected bodies. The genetic relationship between the investigated bodies within groups needs to be considered on the basis of the analysis of orbital evolution of the members of each group over the past several thousand years. The data on the mean heliocentric orbit of the group of meteorite-producing meteoroids enable us to link the group with its likely source, which may be either an asteroid, a family of asteroids or a comet, thereby making it possible to obtain information about the source itself. The search for potential parent bodies of the investigated groups of meteorite-producing fireballs and meteorites was carried out among new near-Earth asteroids. Consequently, several asteroids were selected in each group with the following criteria of the similarity between the asteroid orbit and mean orbit of the respective group: DD ≤ 0.06, DSH and DN ≤ 0.12.